2011
DOI: 10.1016/j.ydbio.2010.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Radial glia regulate Cajal–Retzius cell positioning in the early embryonic cerebral cortex

Abstract: The organization of neocortex, along its radial axis, into a six-layered structure is one of the most exquisite features of the brain. Because of their strategic localization in the marginal zone, and their expression of reelin, a signal that controls spatial ordering of cortical layers, Cajal-Retzius (C-R) cells play a crucial role in cortical patterning along this axis. Yet, it remains less well understood how C-R cell targeting itself is regulated. At the onset of corticogenesis when C-R cells first arrive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…Peroxidase conjugated secondary antibodies were purchased from Santa Cruz Biotech. Staining procedures were performed as described previously [32], and sections were mounted with Fluoromount G medium (Southern Biotech, Birmingham, AB) and analyzed under a Nikon eclipse Ti microscope or an Olympus confocal microscope. For 3-D reconstruction, NIH ImageJ software was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Peroxidase conjugated secondary antibodies were purchased from Santa Cruz Biotech. Staining procedures were performed as described previously [32], and sections were mounted with Fluoromount G medium (Southern Biotech, Birmingham, AB) and analyzed under a Nikon eclipse Ti microscope or an Olympus confocal microscope. For 3-D reconstruction, NIH ImageJ software was employed.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that the distribution of CR cells is also mediated by radial glial cells 67 . Indeed, an absence of radial glia results in local displacement of CR cells in layer I 67 .…”
Section: For Details)mentioning
confidence: 99%
“…Indeed, an absence of radial glia results in local displacement of CR cells in layer I 67 . In addition, the expression of Sema3E by radial glia at the subpallium in the lateral ganglionic eminence has been recently suggested 31 .…”
Section: For Details)mentioning
confidence: 99%
“…For example, Cdk5 is required cellautonomously in both (Hirasawa et al, 2004;Ohshima et al, 2007), Dab1 is required only in migrating neurons (Franco et al, 2011), whereas β1 integrins (Belvindrah et al, 2007) and RhoA (Cappello et al, 2012) are radial glia specific. Ccm3 (this study) and Itgb1 mutants display neuronal migration and cortical lamination defects (Graus-Porta et al, 2001;Schmid et al, 2004;Huang et al, 2006;Marchetti et al, 2010), pial detachment of endfeet (Graus-Porta et al, 2001;Kwon et al, 2011) and reactive gliosis (Robel et al, 2009), suggesting a -possibly indirectinteraction that warrants investigation, especially given the association of CCM1 with ICAP1α, which binds the β1 integrin cytoplasmic tail (Zawistowski et al, 2002;Faurobert et al, 2013). On the other hand, RhoA is necessary in radial glia to stabilize the actin and microtubule cytoskeletons, and to maintain the radial glia scaffold (Cappello et al, 2012); thus, our findings that RhoA is activated in Ccm3 conditional mutants could partially explain the migration defects.…”
Section: Discussionmentioning
confidence: 75%